Close together but a world apart: a comparative history of research practices during the formative years of Brazilian academic science (1934-1955) - Ardigó, F; FABIANO ARDIGO (2014)
This thesis compares the ways in which the nationalisation process impacted the research practices of academics from two universities, the University of Rio Grande do Sul and the University of Parana. Systematic comparisons of both institutions located in the South of Brazil has shown that the differences between them were, indeed, significant during pre-nationalisation years. In Brazilian terms, they are ‘close’ together since only seven hundred kilometres separate them. However, the necessity for regionalised studies on the development of academic science is demonstrated in this thesis through a focus on specific faculties that achieved remarkably different research results, despite their geographical proximity. The comparative analysis carried out in this thesis reveals that significant differences existed, such as institutional arrangements, disciplinary boundaries and networks, despite the fact that they were often found under similar academic arrangements. The nationalisation project carried out in 1950 did not alter these differences overnight, but introduced a new element in both settings that would shape their scientific capabilities to this day. Substantial new evidence presented here indicates that in the early 1950s President Dutra, perhaps inadvertently, forced research-minded academics in both universities to consider the possibility of adapting their research projects to their nationalised institutions. Because of the chain of events enabled by this initiative, in later years, these universities became some of the most prominent institutional settings for scientific research in Brazil. A comparative study of the differences and similarities between ongoing practices in these academic settings at the moment of nationalisation indicates that nationalisation did not occur in an historical vacuum; rather, it enhanced and legitimised deeply rooted academic traditions that came to shape local research cultures over the following decades. When this context is explored it becomes clear that an understanding of nationalisation actually lends greater coherence to traditional chronologies of Brazilian academic science.